Patchy Proton Aurora at Mars: A Global View of Solar Wind Precipitation Across the Martian Dayside From EMM/EMUS. Issue 17 (31st August 2022) - Chaffin, Michael S.; Fowler, Christopher M.; Deighan, Justin; Jain, Sonal; Holsclaw, Greg; Hughes, Andréa; Ramstad, Robin; Dong, Yaxue; Brain, Dave; AlMazmi, Hoor; Chirakkil, Krishnaprasad; Correira, John; et al.
Abstract: Proton aurora at Mars are thought to form indirectly, as a result of solar wind proton charge exchange with planetary coronal hydrogen upstream of the bow shock. This charge exchange produces beamed energetic neutral atoms that bypass the induced magnetosphere and cause spatially uniform auroral emission when they collide with the thermosphere. Here we report multiple definitive observations of spatially localized "patchy" proton aurora at Mars using the Emirates Mars Ultraviolet Spectrometer on the Emirates Mars Mission, and characterize the plasma environment during these events using contemporaneous Mars Atmosphere and Volatile EvolutioN mission measurements. Multiple mechanisms are required to explain these observations, including at times the direct deposition of solar wind plasma into the thermosphere, particularly during radial interplanetary magnetic field conditions. Much future work will be needed to assess these mechanisms and understand the impact of these auroral events on Mars atmospheric evolution. Plain Language Summary: Even though Mars does not have a global magnetic field like the Earth, it still possesses multiple kinds of aurora. One of these is proton aurora, which is thought to form mainly by an indirect process that allows a small fraction of the solar wind to rain down on the planet uniformly across the dayside. We present observations of patchy proton aurora at Mars that require a different explanation. By examining multiple Emirates Mars Mission observations of patchy aurora that have different shapes and locations, and combining these images with plasma measurements made by NASA's Mars Atmosphere and Volatile EvolutioN mission, we conclude that a number of processes can produce patchy aurora. This patchy aurora is mostly the result of plasma turbulence, which under some circumstances leads to direct deposition of the solar wind across the entire Martian dayside, with a potentially large impact on long term atmosphere and water loss from Mars. Key Points: We present the first definitive evidence for spatially localized "patchy" proton aurora on Mars Some events support a hypothesis that radial interplanetary magnetic field conditions can produce patchy proton aurora Other events occur during typical solar wind conditions, requiring new formation mechanisms related to sheath plasma turbulence